Influencia del maíz y morocho en las características organolépticas y nutricionales de bebidas fermentadas - León Chica, Dennise Nagelly (2024)
Corn and morocho (traditional Andean corn) are often used as ingredients in the production of fermented beverages, the use of corn and morocho can significantly change the sensory characteristics of fermented beverages, such as flavor, aroma, color and the texture. In addition, they can increase the nutritional value of the drink, since they are rich in starch and other nutrients. Research shows that the nutritional value and fermentability of these beverages are affected by factors such as temperature, pH, and the microbial composition of the fermentation process. In general, the use of corn and morocho in the production of fermented beverages can significantly improve the final sensory and nutritional properties of the final product.